Skyscrapers - Dupré, Judith; Johnson, Philip (New York : Black Dog & Leventhal, 1996)
Skyscrapers is a lavish and appropriately soaring celebration of the world's most spectacular buildings. From the ancient Lighthouse at Alexandria to the Leaning Tower of Pisa, from the Empire State Building to the Petronas Towers in Malaysia, the 50 buildings represented in this magnificent book leap off the page in words and more than 200 rich, duotone images. This unique volume includes facts-at-a-glance for each building, visual comparisons of heights, and quotes from a variety of architects and experts--all accompanying stunning full-page photos of each structure.
Foreword -- Introductory interview with Philip Johnson -- ANCIENT ROOTS: Washington monument, Washington, D.C / Thomas L. Casey -- Home Insurance building, Chicago / William Le Baron Jenney -- Eiffel Tower, Paris / Gustave Eiffel -- Ulm Cathedral, Ulm, Germany / Mathaus Boblinger -- Wainwright Building, St. Louis, Missouri / Louis Sullivan -- Reliance Building, Chicago / Burnham and Company -- Flatiron(Fuller) Building, New York City / Daniel H. Burnham -- Metropolitan Life Insurance Tower, New York City / Napoleon LeBrun & Sons -- Woolworth Building, New York City / Cass Gilbert -- Tribune Tower, Chicago / Raymond Hood and John M. Howells -- Growth of a City: New York -- Barclay-Vesey Building, New York / McKenzie, Voorhees & Gmelin -- Chrysler Building, New York City / William van Alen -- Empire State Building, New York City / Shreve, Lamb & Harmon -- PSFS Building, Philadelphia / George Howe and William Lescaze -- Rockefeller Center, New York City / Reinhard and Hofmeister; Corbett Harrison and MacMurray; Hood and Fouilhoux -- Lever House, New York City / Skidmore, Owings & Merrill -- Alcoa Building, Pittsburg / Harrison and Abramovitz -- Price Tower, Bartlesville, Oklahoma / Frank Lloyd Wright -- Seagram Building, New York City / Mies van der Rohe with Philip Johnson -- Pirelli Tower, Milan / Gio Ponti with Pier Luigi Nervi -- MATERIALS AND TECHNOLOGY: Pan Am Building, New York City/ Emery Roth & Sons, Walter Gropius and Pietro Belluschi -- Marina City, Chicago / Bertrand Goldberg -- Lake Point Tower, Chicago / Schipporeit-Heinrich Associates -- John Hancock Center, Chicago / Skidmore, Owings & Merrill -- Transamerica Pyramid, San Francisco / William L. Pereira -- World Trade Center, New York City / Minoru Yamasaki and Emery Roth & Sons -- Sears Tower, Chicago / Skidmore, Owings & Merrill -- John Hancock Tower, Boston / I.M. Peio & Partners -- United Nations Plaza Hotel, New York City / Kevin Roche John Dinkeloo and Associates -- Peachtree Plaza Hotel, Atlanta / John Portman & Associates -- TOWERS: Citicorp Center, New York / The Stubbins Associates -- 333 Wacker Drive, Chicago / Kohn Pederson Fox Associates -- National Commercial Bank, Jeddah, Saudi Arabia / Skidmore, Owings & Merrill -- AT&T Headquarters, New York City / Johnson/Burgee Architects -- Nations Bank Center, Houston / Johnson/Burgee Architects -- Rialto Towers, Melbourne, Australia / Gerard de Preu and Partners -- First Interstate Bank Tower, Dallas / I.M. Pei & Partners -- Lipstick Building, New York City / Johnson/Burgee Architects -- OUB Centre, Singapore / Kenzo Tange Associates -- Maybank Headquarters, Kuala Lumpur, Malaysia / Hijjas Kasturi Associates -- VISIONARY CITIES: First Interstate Bank World Center, Los Angeles / Pei Cobb Freed & Partners -- Messeturm, Frankfurt / Murphy/ Jahn -- Bank of China, Hong Kong / I.M. Pei & Partners -- Canary Wharf Tower, London / Cesar Pelli & Associates -- Tokyo City Hall Complex, Tokyo / Kenzo Tange Associates -- DG Bank Headquarters, Frankfurt / Kohn Pedersen Fox Associates -- Landmark Tower, Yokohama, Japan / The Stubbins Associates --Petronas Towers, Kuala Lumpur, Malaysia / Cesar Pelli & Associates -- Jin Mao Building, Shanghai, China / Skidmore, Owings & Merrill -- Kuningan Persada Tower, Jakarta, Indonesia / Skidmore, Owings & Merrill -- One hundred tallest buildings.
Includes bibliographical references and index.
Keywords: SKYCRAPERS